Hypoxic Cell-Derived Extracellular Vesicles Aggravate Rectal Injury Following Radiotherapy via MiR-122-5p - Xu, Yiqing; Ge, Yulong; Chen, Xuming; Zhang, Yingzi; Chen, Huanliang; Liu, Dongli; Lu, Yue; Liu, Yong; Tu, Wenzhi (Frontiers in Cell and Developmental Biology, 2022)
Radiation-induced rectal injury is a common side effect of radiotherapy. Hypoxia often occurs after radiotherapy. This study aimed to explore the bystander effect of hypoxia on radiation-induced rectal injury. In vivo, apoptosis increased nearby the highly hypoxic area in the rectal tissues in the mouse models of radiation-induced rectal injury, indicating the potential involvement of hypoxia. In vitro, flow cytometry and Western blotting showed that both hypoxia and hypoxic human intestinal epithelial crypt (HIEC) cell supernatant promoted apoptosis in normoxic HIEC cells. The pro-apoptotic effect of extracellular vesicles (EVs) derived from hypoxic HIEC cell to normoxic HIEC cells was then determined. MiR-122-5p was chosen for further studies through a microRNA (miRNA) microarray assay and apoptosis was alleviated in cells receiving miR-122-5p inhibiting hypoxic EVs. Together, our study demonstrated that the miR-122-5p containing-EVs derived from hypoxic HIEC cells promoted apoptosis in normoxic HIEC cells. Hypoxic EV-derived miR-122-5p plays a critical pathologic role in radiation-induced rectal injury and may be a potential therapeutic target.